Measuring the Impact of Exchange Rate on Industrial Output in Nigeria (European Journal of Marketing and Economics, 2018)
The role exchange rate plays in the determination of industrial output has long been addressed by various scholars in developed and developing countries alike. However, because of its continuous relevance and importance in the determination of the output of the industrial sector, this paper contributes to the body of literatures by investigating the impact of exchange rate on industrial output in Nigeria. Various econometric methods such as the Augmented Dickey Fuller unit root test, the Box Jenkins O.L.S methodology and the Chow break point test were employed on time series data from 1986 to 2016. The empirical findings reveal that albeit, no long run relationship exist between exchange rate and industrial output, the Box Jenkins O.L.S results reveal a positive and significant effect of exchange rate on industrial output in Nigeria. In addition, the Chow break point test affirms that a structural shift actually occurred in the pattern and direction of exchange rate and industrial output in Nigeria from the beginning of the 4th republic in 1999. The study recommends that although, exchange rate drives industrial output in Nigeria but this should be carefully managed to prevent inflationary spiral in prices of goods and services through contagious effect.
Keywords: Exchange Rate, Industrial Output, Fluctuation, Box Jenkins, O.L.S.